2010
DOI: 10.1103/physrevc.82.027601
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of an entangled channel spin-1 system

Abstract: Co-variance matrix formalism gives powerful entanglement criteria for continuous as well as finite dimensional systems. We use this formalism to study a mixed channel spin-1 system which is well known in nuclear reactions. A spin-j state can be visualized as being made up of 2j spinors which are represented by a constellation of 2j points on a Bloch sphere using Majorana construction. We extend this formalism to visualize an entangled mixed spin-1 system.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…For p < 1, the state is seperable for a range of values of θ. It is observed that as p decreases, the region of θ for which entanglement appears also decreases [16].…”
Section: Mixed Spin-1 Statementioning
confidence: 96%
“…For p < 1, the state is seperable for a range of values of θ. It is observed that as p decreases, the region of θ for which entanglement appears also decreases [16].…”
Section: Mixed Spin-1 Statementioning
confidence: 96%